Population of Gruza in past - Vujadinović Snežana; Gajić Mirjana (Glasnik Srpskog Geografskog Društva, 2007)
On the basis of studies of historical material, scientific papers and statistical sources, a survey of the settlement development of Gruza has been presented in this paper. It was pointed to the continuity of population of Gruza with the Serbs from Medieval period to nowadays. Depending on the socio-political and economic circumstances in Serbia, the oscillations of the demographic development were analyzed.